Os cortiços e o urbanismo sanitário da cidade de São Paulo no final do século XIX - Domenicis, Bianca Melzi de (2014)
The coexistence of hygienic and aesthetic concerns in urban changes of the city of São Paulo by the end of the 19th century is indubitable. In this way, the attention of the municipal government with poor collective housings, called cortiços (Portuguese term for beehives ) is part of an extent sanitation plan that searched beauty and health for the environment, i.e. therefore useful to the city‟s welfare and to its promising image. The so called cortiços were the villians for health and moral of the city of São Paulo: a place of crowd, dirt, vicious and poorness. Despite of being undesirable, there has been a great number of these collective housings in the city. Municipal government, based on the Postures Code and the Sanitary Code of 1894, conducted official visits and interdicts as the main way of reducing this social, hygienic and aesthetic illness that took place in São Paulo‟s downtown